2021
DOI: 10.1177/1076029620983902
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dabigatran Treatment on Rotation Thromboelastometry

Abstract: A rapid and reliable assessment of the dabigatran effect is desirable in dabigatran treated patients with uncontrolled bleeding or before acute surgery. The aim of this study was to study the anticoagulant effects of dabigatran in patients with atrial fibrillation (AF) as assessed by the whole blood assays ROTEM, and how data from these methods correlate to plasma dabigatran concentrations measured by Hemoclot. ROTEM was performed with ROTEM Gamma (Pentapharm GmbH, Munich, Germany). The assays used in our stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…VHAs are not sensitive to the effects of FXa inhibitors (apixaban, rivaroxaban, edoxaban) or DTIs. Modified TEG ® and ROTEM ® systems have been described that measure the effects of FXa inhibitors, as well as DTIs [17,50,100,[109][110][111][112].…”
Section: Vha Limitationsmentioning
confidence: 99%
“…VHAs are not sensitive to the effects of FXa inhibitors (apixaban, rivaroxaban, edoxaban) or DTIs. Modified TEG ® and ROTEM ® systems have been described that measure the effects of FXa inhibitors, as well as DTIs [17,50,100,[109][110][111][112].…”
Section: Vha Limitationsmentioning
confidence: 99%
“…Several studies pointed out that thromboelastometric tests were applicable to qualitatively monitor the anticoagulant effect of DOACs [ 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 ] ( Table S3 in Supplementary Materials ) and the reversibility of their activity [ 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 ].…”
Section: Oral Anticoagulation: Antivitamin K Antagonists (Vkas) and D...mentioning
confidence: 99%
“…Regarding the detection of dabigatran anticoagulant activity with a ROTEM device, some studies evaluated ROTEM reagents in patients treated with dabigatran compared with healthy blood donors (controls) [ 138 , 139 , 140 ] or analyzed the correlations between ROTEM results and dabigatran plasma concentration [ 142 , 143 , 144 , 145 , 146 , 147 , 148 ].…”
Section: Oral Anticoagulation: Antivitamin K Antagonists (Vkas) and D...mentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro spiking studies demonstrated a DOAC dose-response effect in ROTEM CT, which was most pronounced for the EXTEM assay (35). Similar effects were observed in vivo in patients treated with a DOAC or VKA (36,39,(41)(42)(43), hinting that ROTEM may be suitable to monitor anticoagulant drug concentrations. Although EXTEM CT had almost perfect discriminatory ability in the current setting, the observed AUC (0.979) did not outperform the PT assay (Table 2).…”
Section: Discussionmentioning
confidence: 60%